Dutch solidarity workers (cooperantes) in Mozambique present a gift in support of Mozambique's defence capacity to president Machel. . F.l.t.r.: Westerveld, Machel, Gerdes, Jansen, van Albada
Dutch solidarity workers (cooperantes) in Mozambique present a gift in support of Mozambique's defence capacity to president Machel. F.l.t.r.: Westerveld, Machel, Gerdes, Jansen, van Albada.